Analysis of the circulating myeloid‐derived suppressor cells during androgen deprivation therapy for prostate cancer. Issue 6 (1st August 2021) - Kohada, Yuki; Kaiho, Yasuhiro; Takeda, Kazuya; Kuromoto, Akito; Ito, Jun; Teishima, Jun; Nakamura, Yasuhiro; Kaifu, Tomonori; Nakamura, Akira; Sato, Makoto
Abstract : Introduction: The present study showed the involvement of immunosuppressive myeloid‐derived suppressor cells during the disease progression in a 69‐year‐old man with a prostate cancer. Case presentation: The patient with metastatic PC (cT4N1M1ab) was initially treated with primary androgen deprivation therapy for 5 months and then chemotherapy with docetaxel, but he expired at the 8th month. In order to investigate whether myeloid‐derived suppressor cells are implicated in the cancer exacerbation during androgen deprivation therapy, we assessed the long‐term changes in peripheral blood myeloid‐derived suppressor cell fractions by using flow cytometry. While prostate‐specific antigen levels decreased after androgen deprivation therapy, the population of each myeloid‐derived suppressor cell subsets increased during disease deterioration. Conclusion: Increase in myeloid‐derived suppressor cells populations was correlated with prostate cancer progression.